Construction of a Microfluidic Platform for Quantitative Detection of Multiple Fusarium Toxins Based on Upconversion Encoded Microspheres - Shengjie WANG; Yongli YE; Jingdong SHAO; Xiulan SUN; Jiadi SUN (Shipin gongye ke-ji)
To achieve simultaneous and rapid detection of multiple mycotoxins, a microfluidic chip based on upconversion fluorescent-coded microspheres was constructed and integrated with in vitro diagnostic equipment to develop a quantitative detection platform for mycotoxin. The platform employed multi-color upconversion fluorescent-coded microspheres as detection probes and utilized microfluidic chips as detection carriers. It collected images under a dual-wavelength microscope system of the multi-color upconversion fluorescent-coded microspheres and derived the types and contents of toxins through algorithmic analysis of the obtained optical signals. The application effect of the established platform was verified by using corn flour as the food matrix and analyzing deoxynivalenol (DON), T-2 toxin, and fumonisins B1 (FB1). The average diameter of the prepared three-color upconversion nanoparticles was 28.81 nm, the average diameter after wrapping the inert shell was 41.26 nm, and the average diameter of the upconversion coded microspheres obtained after swelling was 10 μm. The optimized ratios of the three kinds of probe antigen antibody secondary antibodies are as follows: DON: 1:50, 1:100, and 1:50, T-2: 1:200, 1:400, and 1:200, FB1: 1:50, 1:100, and 1:50. The detection limits of DON, T-2, and FB1 were 41.35, 0.5044, and 35.45 ng/mL, respectively, with a standard addition recovery from 90.76% to 114.82%. In conclusion, the established mycotoxin detection platform provides an effective way to avoid mutual interference in multiple detections, and it can rapidly and accurately obtain quantitative analysis results.